SERTIFIKASI ISO 9000 DAN KINERJA KEUANGAN PERUSAHAAN - Imam Setijawan (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
This study intend to find about the influence of ISO 9000 certification toward the firm financial performances. The purpose of the study is to find how ISO 9000 certification influences firm financial performances. Thirty six companies that publish their ISO 9000 certification were used as research samples.Using ANOVA analysis, the study find that there is significant differences before and after ISO 9000 certification within firm financial performances and among firm with and without ISO 9000 certification. The result of regression models analyzing shows that ISO 9000 cetification has positif influence toward the firm financial performances but not significant.